2011
DOI: 10.1590/s1517-83822011000300010
|View full text |Cite
|
Sign up to set email alerts
|

Triple inoculation with Bradyrhizobium, Glomus and Paenibacillus on cowpea (Vigna unguiculata [L.] walp.) development

Abstract: The use of microorganisms to improve the availability of nutrients to plants is of great importance to agriculture. This study aimed to evaluate the effect of triple inoculation of cowpea with arbuscular mycorrhizal fungi (AMF), plant growth-promoting bacteria (PGPB) and rhizobia to maximize biological nitrogen fixation (BNF) and promote plant growth. The experiment was conducted in a greenhouse using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
2
3
0
1
Order By: Relevance
“…It appears that synergistic effect of LPGPR1 might be due to release of IAA and further P.indica contributed in enhanced seed germination and plant height. Our results for improvement in seed germination are well in line with earlier findings in chickpea (Ponmurugan and Gopi 2006;Martinez-Viveroz et al 2010 andSharma et al 2007) and cowpea (Lima et al 2011). In earlier study, it was investigated that Mesorhizobium cicer and LPGPR1 used in the present study are known to produce IAA (Kaur and Sharma 2013).…”
Section: Growth Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…It appears that synergistic effect of LPGPR1 might be due to release of IAA and further P.indica contributed in enhanced seed germination and plant height. Our results for improvement in seed germination are well in line with earlier findings in chickpea (Ponmurugan and Gopi 2006;Martinez-Viveroz et al 2010 andSharma et al 2007) and cowpea (Lima et al 2011). In earlier study, it was investigated that Mesorhizobium cicer and LPGPR1 used in the present study are known to produce IAA (Kaur and Sharma 2013).…”
Section: Growth Parameterssupporting
confidence: 92%
“…Significantly high N content was recorded in MR+PI+LPGPR1 (1.79 % and 1.85 %) followed byMR + PI + LK884 (1.77 % and 1.80 %) and MR+PI+LPGPR2 (1.73 % and 1.74 %) in desi PBG1 and kabuli BG1053, respectively over MR alone treatment. Improvement in total N content is well in line with previous findings in chickpea (Nautiyal et al 2010) and soybean (Lima et al 2011) where different bio-inoculant combinations as P.indica+PGPR, AMF+Azospirillum and Bradyrhizobium sp.+Glomus etunicatum, respectively. Higher P content was observed in P. indica alone treatment as compared to Mesorhizobium cicer alone.…”
Section: Endophytic Dependency (Ed) %supporting
confidence: 90%
“…and Piptadenia paniculata Bentham) and found that these two species depend on mycorrhiza for satisfactory growth and nodulation with rhizobia. The synergy between the mycorrhizal fungi and rhizobia microsymbionts on legumes has been well documented in several studies (Mergulhão et al 2001 ;Diniz et al 2002 ;Jesus et al 2005 ;Kaschuk et al 2010 ;Lima et al 2011 ;Mendes Filho et al 2011 ). However, according to Scotti ( 1997 ), the benefi t of these microorganisms to the host plant depends on the compatibility between the strain of rhizobia and mycorrhizal fungi inoculated.…”
Section: Mycorrhizal Infection Of Legume Roots To Stimulate Nodulationmentioning
confidence: 82%
“…BR 17. Lima et al (2011) observaram que os tratamentos sem inoculação das sementes proporcionaram colonizações de rizóbios semelhantes aos tratamentos com adição de diferentes estirpes, sendo possível afirmar a existência de bactérias nativas.…”
Section: Methodsunclassified